STRATEGI PEMASARAN PULAU PANIKI UNTUK MENINGKATKAN KUNJUNGAN WISATAWAN DI DESA KULU KABUPATEN MINAHASA UTARA - Husain, Yusuf Surya; Takaendengan, Mita Erdiaty; Tuwaidan, Altje E; Lumare, Mercy Ariane; Rondonuwu, Diane Olga (HOSPITALITI DAN PARIWISATA, 2026)
This study discusses efforts to design effective marketing strategies to increase the number of tourist visits to Paniki Island, located in Kulu Village, Wori District, North Sulawesi. The island holds significant potential as a marine tourism destination due to its natural beauty, well-preserved mangrove ecosystems, and serene atmosphere. However, the development of tourism on Paniki Island is still hindered by insufficient supporting facilities, limited transportation access, and inadequate promotion. Using a descriptive qualitative approach and SWOT analysis, data was collected through field observations and in-depth interviews with tourists and local community leaders. The research findings indicate that Paniki Island's main strengths lie in its natural beauty and educational tourism potential, while its primary challenges are the lack of facilities and accessibility. Opportunities that can be leveraged include government support, the trend toward nature-based tourism, and the potential for cross-sector collaboration. Meanwhile, threats include competition with other destinations and the risk of environmental damage due to unsustainable management. Based on these findings, a WO (Weakness–Opportunity) strategy is recommended, which involves leveraging external opportunities to address internal weaknesses. Suggested steps include improving facilities, intensifying digital promotion, involving local communities in tourism management, and developing conservation-based tourism. With the implementation of the right strategy, Paniki Island has the potential to become a sustainable flagship tourism destination that provides economic benefits for the surrounding community.